VD_FINDINFO AI 405/09 - 253/2011 vom 23. Mai 2011 - VD Tribunal cantonal (2011)
PRESTATION D'INVALIDITÉ, RECONVERSION PROFESSIONNELLE, TOXICOMANIE, EXPERTISE PSYCHIATRIQUE | 17 LAI, 8 LAI, 16 LPGA, 7 LPGA, 8 LPGA